Site of Memory and Mourning: Metaphor of War in Atiq Rahimi’s Selected Novels - Younas, Zahida (Journal of Research in Humanities, 2024)
The study undertaken analyzes three novels named as Earth and Ashes, A Thousand Rooms of Dream and Fear, and The Patience Stone, written by Atiq Rahimi. These novels tell the stories of families affected by the 1979 war. There is no direct reference to war and violence however, war keeps popping up in the textured background during the narration of the normal experiences of characters in the novels. These novels are enriched with the metaphors embedded in texts that complement the voice which is absent and yet it makes its presence felt throughout the text. The objective of the paper is to bring forth the role of metaphors in war literature. It concludes that metaphors are significant as on the one hand, they create a site for memory for both the part of reader and writer, yet on the other hand, they evoke pathos which invites the reader to mourn the loss of the war-torn community. This study is qualitative in nature and is conducted through the close textual analysis of all the mentioned texts under the lens of theories related to metaphors, war, memory and mourning۔